NICHO CLIMÁTICO COMO MODELADOR DO PADRÃO DE DISTRIBUIÇÃO DAS ESPÉCIES ARBÓREAS “FRIAS” NA REGIÃO DA BACIA DO PRATA - TOMAZINI, Rita Cassiana Molmelstet; RIVABEN, Rodrigo Cyrino; CARDINAL, Renan Henrique Silvestre; AZEVEDO, Evelyn Mayara Silva; PONTARA, Vanessa; BUENO, Marcelo Leandro (ANAIS DO ENIC, 2025)
-